A Comparative Study of Gold Price Movements in Indian and Global Markets - Gaur, Arti; Bansal, Monica (Indian Journal of Finance, 2010)
Since the earliest times, gold has been important for mankind. The basic reason for this being its unique physical properties. Gold as a commodity, as a currency, continues to play its ancient role as the only true standard of value in times of war or crisis. History tells us that only gold retains its value during war; change of empires and govt. and at the time of crisis. Although now officially, gold held to be of only industrial value, gold is the oldest and most respected currency in the world and only one respected currency in the world when national paper money lose value. That is why every central bank of any significance buys and holds goods in reserve in a world of almost universal paper money. The monetary use of gold, along with silver has been very wide spread since ancient times. Gold and silver coins have been most readily acceptable medium of exchange due to intrinsic values of the two metals. The major problem in this use of gold as a coinage metal is its short supply. It is produced only by a few countries mainly South Africa (producing 3/4th of the total world production) Soviet Union, Canada, USA, Ghana, Philippines and Australia. In India gold has maintained an important presence since very early times.